Lithium-ion Battery Energy Storage Digital Twin System and Applications - Zhang, Zhi; Zhou, Zhaoming; He, Yanqin (Scientific Journal of Technology, 2026)
Under the background of large-scale development of new energy, the operation and management of lithium battery energy storage systems face many challenges. Digital twin technology provides effective solutions for the intelligent upgrading of energy storage systems. This article focuses on the research of digital twin technology for lithium battery energy storage. Firstly, it clarifies the core connotation and composition architecture of digital twin technology, and then focuses on sorting out its research achievements in key areas such as model construction, real-time monitoring, life monitoring and management, and application scenarios. The model construction adopts a "bottom-up" multi-scale modeling and hybrid driving strategy, which can achieve accurate simulation of multiple physical fields; Real time monitoring relies on the "edge computing+5G+industrial Ethernet" architecture and hybrid data fusion algorithm to ensure the real-time and reliability of data transmission; Establish a "assessment prediction maintenance" full chain control mode for life management; This technology has been successfully applied in multiple practical scenarios such as power grid peak shaving and frequency regulation. Combined with monitoring practice, it has been shown that the core indicators of the constructed system, such as simulation accuracy and fault warning accuracy, meet the design standards, which can significantly improve the operational efficiency of energy storage power stations and reduce maintenance costs. Finally, summarize the core advantages and current problems of this technology, and look forward to future research directions such as multi-scale modeling optimization and cross domain technology integration, providing theoretical support and practical reference for the large-scale promotion and application of lithium battery energy storage digital twin technology.